COMPARATIVE LETHAL IMPACT OF GLYPHOSATE AND PARAQUAT ON AFRICAN MOUND-BUILDING TERMITES (Macrotermes bellicosus Smeathman) (FUDMA JOURNAL OF SCIENCES, 2022)
In Nigeria, glyphosate and paraquat are common herbicides employed for weed control because they are cost-effective in controlling weeds. It has been shown that, herbicides released into the environment can indirectly affect non-target species, often in harmful ways. We thus investigated the lethal effects of Force up® (glyphosate) and ParaQ® (paraquat) on workers of African mound-building termites (Macrotermes bellicosus Smeathman). The worker termites were treated with 30µl of glyphosate and paraquat at different concentrations viz; 25, 12.5, 6.25, 3.13 and 1.56 ml per 500 ml of water, while distilled water was used as control. Mortality of termites was recorded for 12 and 24 hrs after exposure. Data collected were subjected to variance analysis and probit regression. Results showed that glyphosate caused 48 - 88% mortality, while paraquat caused 36 - 96% mortality after 24 hrs exposure. The mortality was not dose-dependent as 12.5ml of glyphosate and paraquat exerted higher percentage of mortality than 25ml concentration. Conversely, the mortality increased after 24 hrs indicating time-dependent mortality. The toxicity index, i.e. (LC50 and LC90), was 16.82ml and 14.87ml for glyphosate and 2.63ml and 2.196ml for paraquat after 24 hrs of exposure. This apparently shows that paraquat is highly toxic to M. bellicosus at concentrations lower than the recommended rate. These findings calls for the re-evaluation of the use of paraquat-based herbicides in weed control as it negatively impacts termites populations which are key beneficial non-targets
Keywords: Glyphosate, Herbicides, Macrotermes bellicosus, Paraquat, Toxicity